Epidemiology of Anatomical Variations in the Maxillary Sinus Drainage System and the Impact of Concha Bullosa - Shokuhifar, Mohammadreza; Yousefimanesh, Hojatollah; Gandomi, Shiva; Soleimani, Zeinab; Hosseini Behbahani, Hanie (Galen Medical Journal, 2024)
Background: The ostiomeatal complex (OMC) is an important anatomical structure which contains the maxillary ostium and infundibulum; sinus drainage is performed through this route. Concha bullosa, which is defined as pneumatization of the middle concha, may lead to drainage disorders and sinusitis following alterations in the OMC; hence, the purpose of this study was to investigate the effect of presence of concha bullosa on the infundibulum length and ostium height using cone-beam computed tomography (CBCT). Materials and Methods: This cross-sectional study evaluated 208 CBCT scans of 416 maxillary sinuses, which were retrospectively selected from the records available in the CBCT archives. Measurement of infundibulum length and maxillary ostium height were compared based on the presence of concha bullosa. Results: Out of 416 sinuses, 184 (44.2%) had concha bullosa. There was no significant relationship between concha bullosa and age or gender (P>0.05). However, significant differences were observed in infundibulum length and ostium height between genders, with males having longer infundibulum lengths (right: 15.59 mm, left: 15.54 mm, total: 15.56 mm, P<0.001) and higher ostium heights (right: 31.68 mm, left: 32.30 mm, total: 31.99 mm, P=0.001). Concha bullosa presence significantly affected infundibulum length and ostium height on the right side, with shorter lengths (11.83 mm vs. 13.47 mm, P=0.004) and higher heights (30.69 mm vs. 28.51 mm, P=0.001) in those with concha bullosa. No significant correlations were found between age and infundibulum length or ostium height (P>0.1). Gender-specific differences were noted, with females showing significant impacts on the right side and males on both sides. Conclusion: In the present study, presence of concha bullosa shortened the infundibulum length and increased the ostium height. Also, the infundibulum length and ostium height were greater in males than females.